Implementation of Islamic Business Ethics in Increase welfare Trader Post Pandemic ( Study The case on UMKM Lamongan ) - Miftahal Anjarsabda Wira Buana; Akmalur Rijal; Moh. Ah. Subhan ZA; Khotijatul Khoiriyah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
In economy Islamic , business And ethics No must looked at as two opposites , cause business which is symbol from affairs mundane is also considered as integral part of things that are investment afterlife . That is , if orientation business And effort investment hereafter ( intended as worship And is totality obedience to God ), then business with itself must in line with based on moral principles faith to afterlife . Even in Islam , understanding that business Alone No restricted affairs world , however covers all activity We in world that is